Effect of eight weeks of selected aerobic exercise on Apa proteins and lipo proteins in 10-11 years childrens of Tehran - حسن برآبادی; فاطمه سلامی; علی برآبادی (Shahid Beheshti University, 2010)
The purpose of this study was to examine the effect of an 8-week selective aerobic exercise oncardio-vascular risk factors and anti-risk factors in children with aged between 10 -11 years old.The subjects were 30 non-athlete students whom were chosen randomly from volunteers. Wedivided subjects to two groups, each 15 subject, of experimental group and control group. Theexperimental group exercised for a period of 8 weeks with three sessions of exercise of 1 hour withthe 60-70 percent of HRmax and each group was controlled nutritionally 3 days before bloodsampling. The sampling was carried out 24 hours before and after each exercise period for bothgroups to examine some blood factors and body such as HDL-c, LDL-c, VLDL-c, TG, TC, apo-A,apo-B, LBM, BMI, weight and height. Data were analyzed by using the descriptive statistics andindependent-sample t-test. Results showed that following 8 weeks aerobic exercise no anysignificant effect was found on the concentrations of HDL-c, VLDL-c, TC/HDL-c and TC inexperimental group, but the differences in the concentrations of TG, LDL-c, apo-A, apo-B, LDLc/HDL-c and apo-A/B were significant. Finally, according to findings, this type of aerobic exercisedecreases some of the risk factors of cardio-vascular diseases and increases the anti risk factors. So,it seems that this type of exercises is useful for having healthy body.